Homilies on Isaiah - Origen (The fathers of the church, 2021)
"The early Christian theologian Origen preached this series of nine homilies on the Old Testament book of Isaiah between the years 245 and 248 in the city of Caesarea in Roman-occupied Palestine. In these homilies Origen utilizes his characteristic approach to exegesis by providing interpretations on three levels: literal, moral, and allegorical. His main theme is that Christian believers must progress in their own moral cleansing and in achieving deeper understanding in order to arrive at spiritual union with the Trinity. His interpretation of Isaiah's vision in Isaiah 6 is that the two Seraphim represent the Son of God and the Holy Spirit appearing on both sides of the Father's throne, and in this way the entire Trinity is represented. The original Greek of these homilies was lost, but they survive in Latin translation, a translation probably produced by St. Jerome, a scholar of the ancient Church. In this book, Elizabeth Ann Dively Lauro has translated into English the ancient Latin translation of the original Greek homilies by Origen"--